The Influnce of KWL Strategy Use in Teaching Reading for EFL Learners in Class Room - Endang Haryanto (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2019)
Reading is a process to to get both the information and knowledge from written sources or text. To make it easiers there are some applicable strategies. Based on some related literatures, KWL can be implemented in teaching reading for EFL learners in class room with varied reading skill levels. Hence this strategy assumed is appropriate use in Indonesian school context. This reasearch is intended to investigate how effective the strategy in helping leraners to enhanch their ability in reading. The samples of this study were the second year students of SMAN 07 South Bengkulu in 2019. The research design use is experimental study with expemental and control class. From the result of the study the data showed that the students taught with KWL achieved better reading comprehension than those were not taught with the strategy.